PENGETAHUAN DAN SIKAP KELUARGA DENGAN PERILAKU PENCEGAHAN DEMAM BERDARAH DENGUE - Sanggelorang, Tessalonika C.; Rakinaung, Natalia Elisa; Polii, Grace Benedikta (Lasalle Health Journal, 2024)
Introduction: In recent years, dengue cases have become a particular concern in various places, the increasing cases of dengue fever indicate the need for greater focus on prevention. Dengue Hemorrhagic Fever (DHF) is a disease condition caused by dengue virus infection which can be transmitted through mosquito bites. Mosquitoes that can spread the dengue virus are spread throughout almost all of Indonesia. Objective: To determine the relationship between the level of knowledge and family attitudes towards Dengue Hemorrhagic Fever prevention behavior in Bulo Village, Wori District. Method: This research uses quantitative research with a correlation research type. The population in this study is the number of families in Bulo Village, Wori District with a population of 293 families. The number of samples in this study was 169 respondents obtained using the Slovin formula. The method used in this research is simple random sampling. Results: From the results of the bivariate test using the Spearman rank test, it was found that there was a significant relationship between the level of knowledge and dengue prevention behavior (p-value = 0.021) and there was no significant relationship between attitude and dengue prevention behavior (p-value = 0.981). Conclusion: The level of knowledge and dengue fever prevention behavior have a significant relationship, while family attitudes and behavior do not have a significant relationship.